2017
DOI: 10.1016/j.msec.2017.02.060
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of Ti-27.5Nb alloy made by CLAD® additive manufacturing process for biomedical applications

Abstract: Biocompatible beta-titanium alloys such as Ti-27.5(at.%)Nb are good candidates for implantology and arthroplasty applications as their particular mechanical properties, including low Young's modulus, could significantly reduce the stress-shielding phenomenon usually occurring after surgery. The CLAD® process is a powder blown additive manufacturing process that allows the manufacture of patient specific (i.e. custom) implants. Thus, the use of Ti-27.5(at.%)Nb alloy formed by CLAD® process for biomedical applic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 29 publications
0
26
0
Order By: Relevance
“…The vast majority of the investigation in the field of AM concerns the influence of the processing parameters on the properties and microstructure of the alloys [ 18 , 55 , 56 ] or the fabrication of porous structures [ 11 , 57 ]. Fischer et al [ 58 ] conducted cyclic tests on Ti-27.5Nb fabricated using the CLAD technique but no evidence of superelasticity was reported. The presented results revealed that it is possible to obtain relatively good superelastic properties, induced at a high stress near 700 MPa, in alloys fabricated using AM techniques; however, it is necessary to include the effect of oxygen contamination during the development of the alloy composition.…”
Section: Resultsmentioning
confidence: 99%
“…The vast majority of the investigation in the field of AM concerns the influence of the processing parameters on the properties and microstructure of the alloys [ 18 , 55 , 56 ] or the fabrication of porous structures [ 11 , 57 ]. Fischer et al [ 58 ] conducted cyclic tests on Ti-27.5Nb fabricated using the CLAD technique but no evidence of superelasticity was reported. The presented results revealed that it is possible to obtain relatively good superelastic properties, induced at a high stress near 700 MPa, in alloys fabricated using AM techniques; however, it is necessary to include the effect of oxygen contamination during the development of the alloy composition.…”
Section: Resultsmentioning
confidence: 99%
“…Authors have demonstrated the great metallurgical bonding due the consecutive remelting (Mahamood and Akinlabi, 2015) ; Farayibi et al have demonstrated the feasibility of functionally graded Ti6Al4V wire and WC powder for different powder feed rate of WC. The addition of WC improve hardness and wear resistance (Farayibi et al, 2013) ; Ti-Nb alloys were studied with fixe composition such as Ti-45Nb or Ti-27,5at.%Nb (Fischer et al, 2017; ⁎ Corresponding author. E-mail address: pascal.laheurte@univ-lorraine.fr (P. Laheurte).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the most promising materials are β-phase Ti alloys, which have been widely described in the scientific literature as having an emphasis on cast and forged materials [ 53 , 54 , 55 , 56 ]. They provide increased cell viability and improved mechanical compatibility with the cortical bone because of an intrinsically reduced elastic modulus when compared to Ti-6Al-4V [ 19 , 57 , 58 , 59 ], which crystalizes as a mixture of the α and β-phase.…”
Section: Introductionmentioning
confidence: 99%